Release of exosomes in polytraumatized patients: The injury pattern is reflected by the surface epitopes - Weber, Birte; Henrich, Dirk; Schindler, Cora Rebecca; Marzi, Ingo; Leppik, Liudmila (Frontiers in Immunology, 2023)
Background: Trauma is still a leading cause of morbidity and mortality, especially in the younger population. Trauma patients need a precise, early diagnostic to avoid complications like multiorgan failure and sepsis. Exosomes were described as markers and mediators in trauma. The aim of the present study was to analyze, whether the surface epitopes of plasma-exosomes can reflect the injury pattern in polytrauma. Material and Methods: Polytraumatized patients (Injury Severity Score = ISS ≥16, n = 38) were subdivided according to the predominant injury in either abdominal trauma, chest trauma or traumatic brain injury (TBI). Plasma exosomes were isolated via size exclusion chromatography. The concentration and size distribution of the plasma exosomes from emergency room samples were measured by nanoparticle tracking analysis. The exosomal surface antigens were investigated by bead-based multiplex flow cytometry and compared with healthy controls (n=10). Results: In contrast to other studies, we did not observe an increase in the total amount of plasma exosomes in polytrauma patients (1,15x109 vs. 1,13x109 particles/ml), but found changes in the exosomal surface epitopes. We found a significant reduction of CD42a+ (platelet-derived) exosomes in polytrauma patients, CD209+ (dendritic cell-derived) exosomes in the patients with predominant abdominal trauma, and CD11+ (monocyte-derived) exosomes in the patients with chest trauma. The group of patients with TBI was characterized in contrast by an increase of CD62p+ (endothelial/platelet-derived) exosomes (*p<0.05). Conclusion: Our data showed that the polytrauma injury pattern might be reflected by the cellular origin/surface epitopes of plasma-released exosomes immediately after trauma. The observed reduction of CD42+ exosomes in polytrauma patients was not associated with a reduction of total platelets in polytrauma patients.